The Contribution and Reduction of Narrative Theology to Biblical Hermeneutics in the Postmodern Era - Tobing, Oscard L. (Veritas : Jurnal Teologi dan Pelayanan, 2021)
This research examines narrative theology, which began to develop in the 1970s in the United States, and is now widely practiced in theological discourses, including in Indonesia. This theology, sometimes called postliberal theology, uses the postmodern interpretation paradigm, which seeks the meaning â€œin front ofâ€ the text (readers-oriented). The intended readers are the community, who have the same language, culture, and traditions. It turns out that narrative theology, which initially served as a theological reflection on Christianityâ€™s claims to the biblical texts, has shifted into a hermeneutical lens in reading the biblical texts. Using analytical studies of library research and systematic review, the author discusses the contours of narrative theology starting from the thoughts of its pioneers (such as Hans W. Frei, George A. Lindbeck, Stanley Hauerwas, and Sally McFague), describing its characteristics, and evaluating them. The analysis results are presented in two points. The first is an appreciation of the contributions of narrative theology, i.e., simple-practical, confessional-dogmatic, relational, and inductive. The second is an evaluation of some reductive aspects of narrative theology, i.e., postmodern hermeneutics; a disregard of historicity and genre diversity; traditional-dogmatic fideism; sectarianism; and pragmatism.